Persuasive Communication of Tax Officials and Tax Sanctions on Taxpayer Compliance at the Pratama Tax Service Office of Medan Timur - Christian Vinti Parulian Panjaitan; Iskandar Zulkarnain; Rahmanita Ginting (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
The purpose of this study was to analyze the influence and the magnitude of the correlation of the persuasive communication of tax employees and the imposition of tax sanctions on taxpayer compliance at KPP Pratama Medan Timur. The research method used in this research is quantitative method with correlational research type. The study population was all active non-treasurer taxpayers with a total of 75,129 taxpayers. The sampling technique used purposive sampling, calculated using the Taro Yamane formula in order to obtain a sample size of 100 respondents. The results showed that partially persuasive communication of tax employees has an influence on taxpayer obedience at KPP Pratama Medan Timur, this is indicated by Tcount> Ttable (3,299> 1,985). These results also show that partially tax sanctions have no effect on taxpayer obedience at KPP Pratama Medan Timur, this is indicated by Tcount < Ttable (0.424 < 1.985). However, when tested simultaneously, persuasive communication and tax sanctions together have an influence on taxpayer obedience at KPP Pratama Medan Timur, this is indicated by Fcount > Ftable (8.813 > 2.70). These results indicate that the theory used is accepted because the persuasive communication of tax employees combined with the provision of tax sanctions can increase taxpayer compliance at KPP Pratama Medan Timur.